Hypoxia stimulates the proliferation of neonatal rat vascular smooth muscle cells through activation of hypoxia-inducible factor-1α - Lv, Guorong (Int J Clin Exp Med, 2015)
Exposure to an adverse intrauterine environment increases the risk of cardiovascular disease later in adult life. It has been shown that hypoxia plays a critical role in vascular remodeling and directly affects vascular smooth muscle cells functions. In the present study, we aimed to investigate the effect of hypoxia on neonatal rat aorta smooth muscle cells (NRSMCs). Our study demonstrated that hypoxia stimulation at 2% oxygen could significantly enhance NRSMCs proliferation in a time dependent manner. Moreover, hypoxia treatment resulted in an increased percentage in the S + G2/M phase and decreased apoptosis rate in NRSMCs. On the molecular level, the protein levels of pro-apoptotic proteins BNIP3 and bax were obviously reduced, while the anti-apoptotic factor bcl-2 was enhanced under hypoxia condition. Furthermore, we found that hypoxia activated hypoxia-inducible factor-1α (HIF-1α) expression and subsequently promoted NRSMCs proliferation. Specific down-regulation of HIF-1α partly abolished the proliferative effect of hypoxia on NRSMCs growth. Taken together, the present study demonstrated that hypoxia treatment promoted NRSMCs growth through activation of HIF-1α, which may contribute to the understanding of the pathogenesis of atherosclerosis.